Decade of climate extremes. (16th July 2013) - Showstack, Randy
Abstract : The first decade of the 21st century was the warmest decade recorded since modern measurements began around 1850, according to a 3 July report by the World Meteorological Organization (WMO). In addition, a pronounced increase in the global temperature occurred over the 4 decades between 1971 and 2010.